Evaluation of 3β-hydroxysteroid dehydrogenase activity using progesterone and androgen receptors-mediated transactivation - Yazawa, Takashi; Watanabe, Yugo; Yokohama, Yuko; Imamichi, Yoshitaka; Hasegawa, Kazuya; Nakajima, Ke-ichi; Kitano, Takeshi; Ida, Takanori; Sato, Takahiro; Islam, Mohammad Sayful; Umezawa, Akihiro; Takahashi, Satoru; et al. (Frontiers in Endocrinology, 2024)
3-Hydroxysteroid dehydrogenases (3-HSDs) catalyze the oxidative conversion of delta (5)ene-3-beta-hydroxy steroids and ketosteroids. Human 3-HSD type 2 (HSD3B2) is predominantly expressed in gonadal and adrenal steroidogenic cells for producing all classes of active steroid hormones. Mutations in HSD3B2 gene cause a rare form of congenital adrenal hyperplasia with varying degree of salt wasting and incomplete masculinization, resulting from reduced production of corticoids and androgens. Therefore, evaluation of the HSD3B2 enzymatic activity in both pathways for each steroid hormone production is important for accurately understanding and diagnosing this disorder. Using progesterone receptor (PR)-and androgen receptor (AR)-mediated transactivation, we adapted a method that easily evaluates enzymatic activity of HSD3B2 by quantifying the conversion from substrates (pregnenolone (P5) and dehydroepiandrosterone (DHEA)) to (progesterone and androstenedione). HEK293 cells were transduced to express human HSD3B2, and incubated medium containing P5 or DHEA.Depending on the incubation time with HSD3B2-expressing cells, the culture media progressively increased luciferase activities in CV-1 cells, transfected with the PR/AR expression vector and progesterone-/ androgen-responsive reporter. Culture media from human and other mammalian HSD3B1-expressing cells also increased the luciferase activities. HEK293 cells expressing various missense mutations in the HSD3B2 gene revealed the potential of this system to evaluate the relationship between the enzymatic activities of mutant proteins and patient phenotype.